If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + 1 = 17 Reorder the terms: 1 + 4p = 17 Solving 1 + 4p = 17 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4p = 17 + -1 Combine like terms: 1 + -1 = 0 0 + 4p = 17 + -1 4p = 17 + -1 Combine like terms: 17 + -1 = 16 4p = 16 Divide each side by '4'. p = 4 Simplifying p = 4
| -3(2y-4)-12=5 | | (m-2)x^2+1=0 | | 7=2t-11 | | 8d=3d+20 | | 3x^2+2y^2-15=0 | | y(x)=2x^3-9x^2+12x-9 | | -2(3-2x)+4=-7 | | [31]=3w+9-8w | | 6(x+2)=65 | | 30+4x= | | (2-3k)x^2+(4-k)x+2= | | 4x+2y=108 | | y=4x^3-3x-2 | | 8s= | | r+4= | | 14.73=-24.23-6.8b | | r+n= | | 15x-10+21x+7=-9-3x+16+x | | 22x+23-17x-16=x-8+2x+27 | | X(1+x)(3-x)=3 | | (x^2d^2-3xd+4)y=x+x^2*lnx | | (x+5)*(x+5)=1280 | | 8-p=1 | | n^3-3n^2+2n-60=0 | | (x+5)*(x+5)*(x+5)=1280 | | 18x+15-15x+26=-4+7+9x+6 | | 12-3(-4-2y)=-5 | | 18x+15+15x+26=-4+7+9x+6 | | 6-5=2 | | 5+8i=0 | | y=tan(6x) | | 12+13=x |